Cognitive performance and stroke-specific quality of life four years after stroke - Ørbo, Marte C.; Friborg, Oddgeir; Anke, Audny; Halvorsen, Marianne Berg; Løkholm, Mari Thoresen; Pedersen, Synne Garder (Frontiers in Rehabilitation Sciences, 2025)
Long-term cognitive outcomes after stroke and their impact on health-related quality of life remain understudied. This study examined associations between cognitive performance and the Stroke-Specific Quality of Life scale (SS-QOL) four years after stroke. Sixty-five individuals (mean age 64 years, 74% male) with mild-to-moderate strokes completed the SS-QOL, the Modified Rankin Scale (mRS) and a neuropsychological test battery. A previously established principal component analysis of the SS-QOL informed division into Cognitive-Social-Mental (CSM) and Physical-Health (PH) components. Most participants reported no or mild disability on the mRS. Relative to age-adjusted norms, the group performed slightly below average across several cognitive domains, with marked variability indicating a subgroup with pronounced deficits. PH scores were high, reflecting minimal physical disability, whereas CSM scores were lower, indicating persistent challenges. CSM scores were associated with reaction time (ρ = .47), verbal memory (ρ = .42) and fine-motor coordination (ρ = .39; all p ≤ .001). PH scores were associated with fine-motor coordination (ρ = .49; p < .001). No significant associations emerged for language, visuospatial abilities, attention or executive functions after correction for multiple comparisons. In summary, associations between cognitive domains and SS-QOL were circumscribed and concentrated within the CSM component. Results indicate that cognitive and psychosocial factors are relevant in long-term recovery. Even selective cognitive deficits could reduce health-related quality of life and warrant follow-up. Generalisability is limited by the small, predominantly male sample, exclusion of individuals with aphasia, severe disability or age >75 years. Replication in larger, more diverse samples is needed.